STRUKTUR BERPIKIR KRITIS SISWA DALAM MENYELESAIKAN MASALAH MATEMATIKA - Muhammad Baidawi; Liza Tridiana Mahardhika; Kusnul Kotimah (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2023)
The purpose of this study is to describe the structure of students' critical thinking processes in solving mathematical problems. This research is a descriptive qualitative research with four research subjects. Based on the results of the study, it was found that 1) the stages of students' critical thinking processes in solving mathematical problems include, a) clarification, b) assessment, c) inference, and d) strategies. 2) Students go through all stages of the critical thinking process in solving problems. 3) Students' critical thinking processes in solving mathematical problems are not always sequential. 4) The critical thinking process of each student is different. 5) stages of thinking starting from the assessment stage, clarification, inference then strategies.